Implemantasi Kitab Ta’lim Muta’allim Dalam Membentuk Etika Berbakti Kepada Orang Tua Di Pondok Pesantren Bustanul Muta’allimin Dan Mambaul Quran Pringapus Kabupaten Semarang - Nur Cholisatul Chusna; Naimatus Tsaniyah (SALIHA: Jurnal Pendidikan & Agama Islam, 2021)
Devotion to both parents is obligatory for every child. The obligation of the child to be filial to both parents can be applied and learned through the Koran. Koran is prioritized in Islamic educational institutions, namely Islamic boarding schools. Pondok pesantren is an educational institution that prioritizes moral education, especially morals for both parents, referring to kitan ta'lim muta'allim. The objectives of this study were (1) To determine the ethics of filial piety to both parents in the book Ta'lim Muta'allim (2) To determine the implementation of the book Ta'lim Muta'allim in boarding school Manba'ul Qur'an and Bustanul Muta'allimin.  To achieve this goal, the researcher used field research, namely the researcher conducted direct research on the object under study, namely the management and caregivers of the Bustanul Mua'allimin and Manba'ul Qur'an Islamic Boarding Schools and collected data found in the field. The data collection used by interview, observation, and documentation techniques. The results of this research are as follows: (1) Ethics of filial piety to parents are as follows: Do not cross in front of him, do not occupy his seat, do not start a conversation except with his permission, do not talk a lot next to him, do not ask something boring, do not knock door but be patient until he comes out, seeks the pleasure of the teacher and avoids his anger, upholds his orders as long as he does not violate religious teachings, respects and cherishes his children and anyone associated with him. 2). The implementation of filial ethics for both parents at the boarding school: Tahlil and pilgrimage to the grave, reciting the muta'allimin ta'lim book, giving good examples, praying for parents, respecting parents, appreciating parental gifts, salim/ kissing hands when traveling, helping homework, using polite language, not interrupting when advised